Agile human centered methodologies to develop educational software (2015)
This paper presents a methodological proposal that is based on powerful current approaches to the software development process: agile methodologies (SCRUM, Lean UX), user-centered design (UCD) and user experience design (UXD). Specifically, we have adapted some of the characteristics of the agile methodologies, which have allowed us to produce useful prototypes that are focused on the users while receiving constant feedback from them. The main goal of the proposed methodology is to identify usability problems and UX factors in the early stages of educational software development. Furthermore, we have also applied and validated the proposal during the framework development of an educational software project for users with special educational needs. A specific case taking into account key usability issues to support students with special education needs (SEN) is presented. In conclusion, we state that the proposed methodology could be a good design process philosophy to follow in the development of software projects in general, and in educational projects in particular.